1997
DOI: 10.1104/pp.113.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Internal Detoxification Mechanism of Al in Hydrangea (Identification of Al Form in the Leaves)

Abstract: An internal detoxification mechanism for AI was investigated in an AI-accumulating plant, hydrangea (Hydrangea macrophylla), focusing on AI forms present in the cells. l h e leaves of hydrangea contained as much as 15.7 mmol AI kg-' fresh weight, and more than two-thirds of the AI was found in the cell sap. Using "AInuclear magnetic resonance, the dominant peak of AI was observed at a chemical shift of 11 to 12 parts per million in both intact leaves and the extracted cell sap, which is in good accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
190
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 13 publications
5
190
0
4
Order By: Relevance
“…The organic acid content of root tips was also investigated in response to Al exposure, as internal levels of Al-chelating organic acids have also been implicated in an internal Al tolerance mechanism in buckwheat (Fagopyrum esculentum) and hydrangea (Hydrangea macrophylla; Ma et al, 1997aMa et al, , 1997b. As shown in Figure 2B, exposure to increasing levels of Al elicited a strong (over 3-fold) increase in root tip citrate content.…”
Section: Resultsmentioning
confidence: 99%
“…The organic acid content of root tips was also investigated in response to Al exposure, as internal levels of Al-chelating organic acids have also been implicated in an internal Al tolerance mechanism in buckwheat (Fagopyrum esculentum) and hydrangea (Hydrangea macrophylla; Ma et al, 1997aMa et al, , 1997b. As shown in Figure 2B, exposure to increasing levels of Al elicited a strong (over 3-fold) increase in root tip citrate content.…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al (1997aMa et al ( , 1997c identified forms of aluminumorganic acids compounds in the cell sap of hydrangea (Hydrangea macrophylla) and buckwheat leaves and proposed that these compounds might be sequestered in vacuoles. Later, Shen et al (2002) demonstrated that most aluminum and oxalate in the protoplasts of buckwheat leaves is present in the vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…The well-documented exclusion mechanism is to prevent aluminum from entering root cells by secretion of organic acid anions by the root apex, resulting in the formation of stable nonphytotoxic chelates with aluminum (Kochian, 1995;Ryan et al, 2001;Ma and Furukawa, 2003). The internal detoxification of aluminum is primarily based on the storage of aluminum in the vacuole as aluminum-oxalate (Ma et al, 1997a;Shen et al, 2002) or aluminum-citrate (Ma et al, 1997b) complexes, thus changing the distribution of aluminum within cells (Ma, 2000;Ma and Hiradate, 2000). Recently, some transporters involved in the aluminum distribution within cells have been identified.…”
mentioning
confidence: 99%
“…Since growth was decreased only by about 5% at that time, it would appear that low amounts of Al can be tolerated at the nucleus with minimal disruptions in function. It is conceivable that internal detoxification processes, perhaps the formation of non-toxic Al complexes (Ma et al, 1997;Watanabe et al, 1998) at the nuclear membrane surface, were helping to depress inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%